Reproductive biology of the bathyal asteroid Ctenodiscus crispatus in the northeastern Pacific. Issue 4 (17th October 2022) - Rist, Sinja; Rice, Lauren N.; Plowman, Caitlin Q.; Fountain, C. Tyler; Calhoun, Avery; Ellison, Christina; Young, Craig M.
Abstract: The mud star Ctenodiscus crispatus has a broad distribution from Arctic waters into the northern Atlantic and Pacific oceans. Populations in the Atlantic are well studied and show oocyte sizes indicative of continuous gametogenesis with aseasonal spawning. In contrast, knowledge on the reproductive biology of Pacific populations is lacking. Thus, this study aims to examine the reproduction of C. crispatus in the northeastern Pacific. We sampled a population from the Pacific Ocean off Oregon and confirmed the species identity through 16S and cytochrome oxidase subunit I ( COI ) genetic barcoding. The majority of adults were 22–27 mm in size. Oocytes were obtained from dissected gonads soaked in a 1‐methyladenine solution and fertilized with spawned sperm. Other individuals were preserved whole in 10% buffered formalin, and oocytes were measured from preserved gonads. Strip‐spawned oocytes had a mean diameter of ~485 μm, consistent with Atlantic populations. Sperm had a mean head diameter and flagellum length of 3.1 and 65.9 μm, respectively. The time between first and second cell divisions was ~2 h, but larval cultures failed, and very few embryos developed to blastulae. Both strip‐spawned and preserved oocytes had a bimodal size‐frequency distribution indicative of semicontinuous gametogenesis. Comparison among individuals showed evidence of asynchrony among the population. This asynchrony and bimodal oocyte distribution may be driven by regular pulses of food, as has been postulated for other populations of this species. The reproductive plasticity seen among populations of this species in different regions could explain how it successfully inhabits such a wide geographic range. Abstract: Der Seestern Ctenodiscus crispatus ist weit verbreitet, von der Arktis bis in den nördlichen Atlantik und Pazifik. Atlantische Populationen sind gut untersucht und weisen Größenverteilungen der Oozyten auf, welche eine kontinuierliche Gametogenese mit saisonunabhängigem Laichen andeuten. Im Gegensatz dazu fehlt das Wissen zur Reproduktionsbiologie pazifischer Populationen. Das Ziel dieser Studie ist es daher die Reproduktion von C. crispatus im nordöstlichen Pazifik zu untersuchen. Wir nahmen Proben einer pazifischen Population vor der Küste Oregons und bestätigten die Art durch DNA Barcoding der 16S ribosomalen DNA und des cytochrome oxidase subunit I ( COI ) Gens. Die Mehrzahl der adulten Tiere war 22–27mm groß. Oozyten wurden aus sezierten Gonaden, welche zuvor in einer 1‐Methyladeninlösung eingeweicht wurden, entnommen und mit abgelaichten Spermien befruchtet. Andere Individuen wurden als ganze in 10% gepuffertem Formalin eingelegt und von diesen wurden Oozyten in den konservierten Gonaden gemessen. Die aus sezierten Gonaden entnommenen Oozyten hatten einen durchschnittlichen Durchmesser von ~ 485 μm, welcher gut mit atlantischen Populationen übereinstimmt. Die Spermien wiesen eine durchschnittliche Kopflänge von 3.1 μm und eine Schwanzlänge von 65.9 μm auf. Die Zeitdauer von der ersten zur zweiten Zellteilung betrug ~2 Stunden. Die Kultivierung der Embryonen scheiterte jedoch und nur wenige entwickelten sich zu einer Blastula. Sowohl die sezierten als auch die konservierten Oozyten wiesen eine bimodale Größenverteilung auf, welche auf eine semi‐kontinuierliche Gametogenese hinweist. Der Vergleich zwischen einzelnen Individuen deutete auf eine Asynchronie innerhalb der Population hin. Diese Ansynchronie und bimodale Größenverteilung der Oozyten könnte eine Folge regelmäßiger Nahrungseinträge sein, so wie es bereits für anderer Populationen dieser Art postuliert wurde. Die beobachtete reproduktive Plastizität diverser Populationen dieser Art in verschiedenen Regionen könnte eine Erklärung für die weite geographische Verbreitung sein.